Teachers’ Ethical Dilemmas at Cristeta Bagano Memorial High School through the Lens of Moral Philosophy - Columna, Rachelle Mae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the ethical dilemmas encountered by teachers and their ethical decision-making approaches at Cristeta Bagano Memorial High School, with emphasis on the influence of demographic characteristics. Anchored on deontology, utilitarianism, and virtue ethics, the study employed a quantitative descriptive-correlational design to analyze relationships among demographic variables, ethical dilemmas, and ethical decision-making frameworks. Data were collected from 40 teacher-respondents using a validated researcher-made questionnaire and were analyzed using frequency, percentage, weighted mean, and Pearson correlation. Findings revealed that teachers commonly experience ethical dilemmas in areas such as student discipline, grading and academic integrity, professional relationships, administrative pressures, and confidentiality. Results further showed that teachers strongly apply virtue ethics, along with deontological and utilitarian principles, in making ethical decisions. Significant positive relationships were found between demographic characteristics and both ethical dilemmas and ethical decision-making approaches, indicating that personal and professional factors influence ethical behavior. The study concludes that ethical decision-making in teaching is multidimensional and shaped by both philosophical frameworks and individual contexts, and recommends the development of targeted ethics programs, clear institutional guidelines, and reflective professional development initiatives. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions) by promoting ethical teaching practices and strengthening institutional integrity in education. It contributes to educational, institutional, and socio-cultural sustainability by enhancing ethical competence, fostering accountability, and supporting the development of fair and inclusive learning environments.